Kerjasama Antar Daerah Dalam Penyediaan Transportasi Publik (Kajian Transportasi BRT Kota Semarang - Kab. Semarang) - Dinanti Putri Pradina; Wiwik Widayati; Turtiantoro . (Journal of Politic and Government Studies, 2014)
Semarang city is one of the major cities in Indonesia that development activities are often traversed the city and the purpose of the buffer zone communities Semarang. So that people need a buffer zone of Semarang city transportation that is reliable, fast, and efficient, as the center of activity is in the center of town. Along with the increasing needs of the transportation increase as well as vehicle ownership in the city, but it is not followed by the addition of road network and adequate road widening, so it is feared there will be traffic jams in many streets in the city of Semarang.            As part of efforts to solve the problems of congestion, the Central of Government through the Department of Transportation, the organization filed a Bus Rapid Transit (BRT) Trans Semarang. With the BRT Trans Semarang as mass transportation is expected to reduce congestion arising from the development of the city itself, because essentially BRT Trans Semarang instead of adding mass transit in the city, but the Bus Rapid Transit can replace three to four mass transportation in the city of Semarang . BRT Trans Semarang Route Corridor II is Mangkang – Pudak Payung, bus lines 3/4 with 22 seats and can accommodate 42 passengers for an area across the city of Semarang and Semarang regency.            In this study, researchers used a qualitative approach that will generate descriptive data. This research was conducted in Dishubkominfo Semarang . The data were obtained through observation, interviews aimed to analyze the pattern of cooperation Municipality of Semarang and Semarang District Government in implementing BRT Trans Semarang public transport between regions. The results of this study is collaboration between Semarang and Semarang in it needs to be underpinned by a statute or treaty between regions, so as to have the force of law binding on both parties. Given the strategic role played by the Provincial Government in the unitary state system, the ability to increase the role and mechanisms of cooperation in this province, including the structure and function of institutional adjustment, should be an important agenda of the government in the future.Keywords: The Cooperation Between Regencies, BRT Trans Semarang Coridor I